Changes in the healthfulness of food and beverage purchases from 2006 to 2022 by outlet type in Mexico - Ana Paula Domínguez-Barreto; Irene Farah; Nancy López-Olmedo; Carolina Pérez-Ferrer; Yenisei Ramírez-Toscano; Brent A. Langellier; M. Arantxa Colchero; Juan A. Rivera-Dommarco; Tonatiuh Barrientos-Gutiérrez; Dalia Stern (BMC Medicine)
Abstract Background To better inform retail food environment policies in the global south, it is necessary to further understand the healthfulness of food and beverages purchased by type of food outlet over time. Methods Using repeated cross-sectional data from the National Income and Expenditure Survey (ENIGH) in Mexico (2006 to 2022), we estimate the percentage of food and beverage purchases by processing level for each food outlet for the overall population and stratify by education (proxy of socioeconomic status) and urbanicity levels. Results In 2006, the food outlets with the largest proportions of ultra-processed foods purchases were chain convenience stores (49%), small neighborhood stores (37%), and supermarkets (35%). In contrast, the outlets with the highest proportions of minimally processed food purchases were street markets (83%), public markets (81%), and specialty stores (75%). Over time, households increased the proportion of expenditure in minimally processed foods in supermarkets and slightly in small neighborhood stores (49 to 54% and 46 to 47%, respectively). Conversely, the proportion of expenditures in minimally processed foods decreased from 70 to 62% in street vendors. Households without formal education and residing in rural areas increased their minimally processed food purchases in specialty stores, but decreased in street vendors, acquaintances, and public markets. Households with higher education and residing in more urbanized areas increased their purchases of minimally processed foods in supermarkets and small neighborhood stores and decreased in street vendors. These households also increased their purchases in ultra-processed foods in chain convenience stores. Conclusions There is a wide range of food outlets in Mexico, each with varying levels of healthfulness. While purchases in supermarkets have become healthier, particularly among higher socioeconomic households and in larger cities, small neighborhood stores have also shown improvements, especially in lower-income households and smaller cities. Since no outlet exclusively sells healthy or unhealthy foods, policies should focus on where people make the majority of their purchases and address healthfulness variations based on education level education and urbanization.